Comparison of multi-institutional pre-treatment verification for VMAT of nasopharynx with delivery errors. (September 2018) - Pogson, E.M.; Arumugam, S.; Hansen, C.R.; Currie, M.; Blake, S.J.; Roberts, N.; Carolan, M.; Vial, P.; Alharthi, T.; Holloway, L.; Thwaites, D.I.
Highlights: Not all clinically unacceptable errors are detected. Majority of errors were detected combining ArcCHECK and ion chamber measurements. Combining ion chamber measurements with gamma analysis is recommended. Gamma analysis was least sensitive to negative field size errors. Optimum gamma settings varied across institutions. Abstract: Purpose: Measurement-based pre-treatment verification with phantoms frequently uses gamma analysis to assess acceptable delivery accuracy. This study evaluates the sensitivity of a commercial system to simulated machine errors for three different institutions' Volumetric Modulated Arc Therapy (VMAT) planning approaches. Methods: VMAT plans were generated for ten patients at three institutions using each institution's own protocol (manually-planned at institution 1; auto-planned at institutions 2 and 3). Errors in Multi-Leaf Collimator (MLC) field size (FS), MLC shift (S), and collimator angle (C) of −5, −2, −1, 1, 2 and 5 mm or degrees were introduced. Dose metric constraints discriminated which error magnitudes were considered unacceptable. The smallest magnitude error treatment plans deemed clinically unacceptable (typically for a 5% dose change) were delivered to the ArcCHECK for all institutions, and with a high-dose point ion chamber measurement in 2 institutions. Error detection for different gamma analysis criteria was compared. Results: Not all deliberately introduced VMAT plan errors were detected using a typical 3D 3%/3 mm global gamma pass rate of 95%. Considering all institutions, gamma analysis was least sensitive to negative FS errors. The most sensitive was a 2%/2 mm global analysis for institution 1, whilst for institution 2 it was 3%/3 mm global analysis. The majority of errors (58/59 for institution 1, 54/60 for institution 3) were detected using ArcCHECK and ion chamber measurements combined. Conclusions: Not all clinically unacceptable errors are detected. Combining ion chamber measurements with gamma analysis improved sensitivity and is recommended. Optimum gamma settings varied across institutions.